9-Demethoxy-medicarpin promotes peak bone mass achievement and has bone conserving effect in ovariectomized mice: Positively regulates osteoblast functions and suppresses osteoclastogenesis. (15th August 2015) - Goel, Atul; Raghuvanshi, Ashutosh; Kumar, Amit; Gautam, Abnish; Srivastava, Kamini; Kureel, Jyoti; Singh, Divya
Highlights: DMM, a derivative of natural product medicarpin, possesses bone conserving effect. DMM promotes osteoblast function via activation of P38MAPK/BMP-2 pathway. DMM increases OPG level and decreases transcript level of TRAP in co-culture. DMM increases bone mineral density and new bone formation in SD rats. DMM significantly restores trabecular microarchitecture in OVx mice. Abstract: We report a new bone anabolic and anti-catabolic pterocarpan 9-demethoxy-medicarpin (DMM) for the management of postmenopausal osteoporosis. DMM promoted osteoblast functions via activation of P38MAPK/BMP-2 pathway and suppressed osteoclastogenesis in bone marrow cells (BMCs). In calvarial osteoblasts, DMM blocked nuclear factor kappaB (NFκB) signaling and inhibited the mRNA levels of pro-inflammatory cytokines. DMM treatment led to increased OPG (osteoprotegrin) and decreased transcript levels of TRAP (tartarate resistant acid phosphatase), RANK (receptor activator of NFκB) and RANKL (RANK ligand) in osteoblast–osteoclast co-cultures. Immature female SD rats administered with DMM exhibited increased bone mineral density, bone biomechanical strength, new bone formation and cortical bone parameters. Ovx mice administered with DMM led to significant restoration of trabecular microarchitecture and had reduced formation of osteoclasts and increased formation of osteoprogenitor cells in BMCs. DMM exhibited no uterine estrogenicity. Overall, these results demonstrate the therapeutic potential of DMM for the management of postmenopausal osteoporosis.